Menggali Potensi Lokal melalui Pengembangan UMKM dan Peluang Desa Wisata dalam Pemulihan Covid-19 di Kampung Semanggi, Surabaya - Ermawati, Yuli; Aminatuzzuhro, Aminatuzzuhro; Maulana, Sandi M (STIE Pelita Nusantara, 2022)
Translator Translator Translator Desa Kendung in Surabaya is known as the Kampung Semanggi, because it has a large clover land and a large number of clover traders. Kampung Semanggi has a dream to become a Semanggi Culinary and Educational Tourism Village in the city of Surabaya. The problems experienced by the residents of Kampung Semanggi in general are the lack of ability to utilize local potential, both facilities and synergies with city government programs, lack of marketing for processed clover products, and lack of independent population data processing.In community service carried out by lecturers and students through the Wijaya Putra University Student Community Service Program activities, the team offers solutions by maximizing the local potential of Kampung Semanggi. As a result of the activity, the team has provided Inspiring Clover Cultivation activities, Innovation Training for clover processed products, as well as providing several facilities as a nursery for village tourism potential opportunities by helping facilitate the culinary stands of clover traders which will later be used as the Semanggi Culinary Center and the Kampoeng Semanggi Photo Spot area. For population data problems, the team helped collect and input data through Family Cards for residents and provided socialization of population data processing to 8 RT heads and RW 03 administrators.Keywords: Local Potential, Tourism Village, MSME Development